FIBERS OF THE PREPARATION BIOBARS-M IMPACT ON QUALITY INDICATORS I - Fazliddin Shamsitdinov; Numonov Otabek Urmonvich (Journals Park Publishing, 2023)
When using Biobars-M stimulants during seed treatment and during the flowering and flowering period of cotton on the light gray soils of the Namangan region, there is a significant acceleration of seedling germination compared to the control and standard options. The number of leaves is 1.3, plant height is 10.0 cm. 0.6 units, number of knots 0.8 units, number of bolls 2.5 units, weight of one boll improved by 0.2 units, cotton yield increased due to accumulation of dry mass and increase in leaf surface, with additional application of 5 .6 t/ha of fiber, it was established that the quality indicators of the mass of 1000 seeds were 9.0 g, the fiber yield was 1.4%, and the fiber length was 1.5 mm.
Keywords: cotton variety, preparations Bukhara-102, Uzgumi, Biobars M, growth, development, seedling thickness, yield and quality of cotton.